The development of digital-based training media for tourism and hospitality job training center in Bali - Made Arya Astina; Ni Wayan Rena Mariani; I Wayan Eka Sudarmawan (Universitas Muhammadiyah Magelang, 2021)
This community service activity is a collaboration between IPB International and DPD HILLSI (Association of Indonesian Private Training Institution) Bali which supervise the Job Training Centers in Bali. This activity was held to respond to an urgent need related to distance training that was held as a result of the Covid-19 Pandemic. This distance training needs transformation of training media from conventional to digital. The participants of this community service activity are instructors from Job Training Centre of the tourism and hospitality sector in Bali. This activity, which was held for 3 days, focusing on the development of digital-based media in accordance with current needs. The method of this training was not only lecturing, but also discussion and give many opportunities for the participants to practice their skill, and presenting their media. Participants were given the opportunity to work on a project to make several training media which were presented at the end of the training. To support the project, all participants were provided with supporting facilities, such as internet quota, modules, and clip microphones. After participating this training, participants have understanding of the importance of media in a competency-based training, able to create various digital-based training medias, and distance learning quality improvement.